Juridical Review of Land Disputes Against Unlawful Actions (Case Study Decision No. 27/ Pdt.G/ 2021/ Pn.Spt) - Nur Achmad Azi Ibrahim; R Rizka (Proceeding International Conference Restructuring and Transforming Law, 2023)
Humans and land cannot be separated because human life depends on land. Land has a very important value for humans because almost all human needs are related to land, from birth to death. Humans have an emotional and spiritual connection to land, which is not seen as a commodity with economic value, but also has cultural, customary, economic and spiritual elements that are valuable for the owner. Because of this, land disputes often occur, as in Decision no. 27/ Pdt.G/ 2021/ Pn.Spt. This research uses a normative juridical method by examining library materials related to the decision. The results show that the factors causing land disputes are the lack of regulations regarding land rights and unclear land ownership documents in the past. Therefore, the plaintiff's claim must be declared inadmissible, and the arguments of the claim must be explained specifically to determine what actions violate the law.